Analysis of hygienic and sanitary conditions in establishments that sell purified water in electronic fountains in the city of Assú - RN (Research, Society and Development, 2024)
Consumption of water outside of hygienic-sanitary quality standards can cause a high number of illnesses, from mild symptoms such as: diarrhea, nausea, chills, vomiting, fever, to more serious cases such as typhoid fever, hepatitis A and cholera, caused by by the presence of pathogenic microorganisms and/or their toxins. Given the increase in demand and commercialization of purified water in electronic fountains in the municipality of Assú, the objective of carrying out this research was to verify the hygienic-sanitary conditions in establishments that sell purified water in electronic fountains in the city of Assú – RN. To carry out this study, we used the application of a Check-list control tool based on Resolution No. 173/2006, which provides for the Technical Regulation of Good Practices for the Industrialization and Commercialization of Natural Mineral Water and Natural Water and the Checklist of Good Practices for the Industrialization and Commercialization of Natural Mineral Water and Natural Water. The results reveal that the establishments compared according to the checklist were not in compliance with the standards established by legislation, in which 90% of the establishments were failed, revealing the poor sanitary quality arising from the fountains analyzed. This indicates that water quality outside legal standards is not suitable for human consumption and may cause harm to the consumer’s health. Finally, greater action is needed from the competent public bodies regarding the supervision of these locations, so that they meet the minimum needs to provide a quality product.